(untitled) (Praxis Educativa, 2019)
This article shows the results of a research work whose objective was to identify and discuss excluding categories in History school textbooks, and its pedagogic reception in an interethnic social and educational context, specifically in schools located in the region of the Araucanía in Chile. The research was carried out under a socio-critical paradigm and the methodology used was critical discourse analysis. The sample was a corpus of three textbooks used as didactic resources in 2015. The results allowed as the possibility to set up two excluding categories: linguistic diversity as a result from the meeting of two cultures, and the formation of the national territory/occupation of mapuche territory. Here it seems to predominate a critical pedagogical reception that argues and discusses, with data of the context, the cultural assimetry which promotes the discursive construction of the textbook.